(untitled) (مجلة إضافات إقتصادية, 2025)
This study examines the impact of electronic payment methods on the financial performance of Ooredoo, a Qatari economic institution, during 2017–2024. Customer value was used as an indicator of electronic payments, while revenues measured financial performance. Statistical significance tests confirmed a meaningful correlation, and regression analysis clarified the relationship. The Granger causality test further explained the direction of influence. Results show a statistically significant link, indicating that electronic payment methods enhance Ooredoo’s financial performance, particularly in the long term. Jel Classification Codes: G21, E42, L81.